Laser Thermal Processing of Group IV Semiconductors for Integrated Photonic Systems. Issue 7 (20th May 2021) - Aktas, Ozan; Peacock, Anna C.
Abstract : In the quest to expand the functionality and capacity of group IV semiconductor photonic systems, new materials and production methods are constantly being explored. In particular, flexible fabrication and postprocessing approaches that are compatible with different materials and allow for tuning of the components and systems are of great interest. Within this research area, laser thermal processing has emerged as an indispensable tool that can be applied to enhance and/or modify the material, structural, electrical and optical properties of group IV elemental and compound semiconductors at various stages of the production process. Herein, the recent progress made in the application of laser processing techniques to develop integrated semiconductor systems in both fiber‐ and planar‐based platforms is evaluated. Laser processing has allowed for the production of semiconductor waveguides with high crystallinity in the core and low optical losses, as well as postfabrication trimming of device characteristics and direct writing of tunable strain and composition profiles for bandgap engineering and optical waveguiding. For each platform, the current challenges and opportunities for the future development of laser‐processed integrated semiconductor photonic systems are presented. Abstract : Herein, laser processing of group IV elemental and compound semiconductors via thermal effects induced by continuous wave and pulsed lasers, which have been used to enhance or tailor the material, structural, electrical, and optical properties, is focused on. Applications of laser thermal processing are highlighted in fabrication of photonic systems integrated within fiber and planar platforms, presenting challenges and opportunities.